PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DIDUKUNG APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 192 INPRES TAKKALASI - D. Wulan Azzahra; Ma'ruf M; Andi Muafiah Nur (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
This study aims to determine the influence of problem-based learning model supported by Quizizz application on the learning outcomes of IPA students in 5th grade. This study was a quantitative study using experimental quasi-experimental design with Non-Equivalent Control Gorup Design, with two class groups namely experimental class and control class. The data in this study were analyzed with descriptive statistical analysis techniques and inferential statistics. Results showed that there is an influence of Quizizz app-supported problem-based learning model on the IPA learning outcomes of 5th grade SDN 192 Inpres Takkalasi students. This is shown by the average posttest score of the control class which reached only 67.28 while in the experimental class the mean value of the posttest reached 91.40. Based on the results of the hypothesized independent sample t-test, the sig. (2-tailed) equal variance assumed value obtained 0.000 indicating that 0.000 < 0.05 or in other words H0 was rejected and H1 was accepted, which means that there is an influence of the problem-based learning model supported by Quizizz application on the IPA learning outcomes of 5th grade students.